Copper Metabolism in Naegleria gruberi and Its Deadly Relative Naegleria fowleri - Ženíšková, Kateřina; Grechnikova, Maria; Sutak, Robert (Frontiers in Cell and Developmental Biology, 2022)
Although copper is an essential nutrient crucial for many biological processes, an excessive concentration can be toxic and lead to cell death. The metabolism of this two-faced metal must be strictly regulated at the cell level. In this study, we investigated copper homeostasis in two related unicellular organisms: nonpathogenic Naegleria gruberi and the “brain-eating amoeba” Naegleria fowleri. We identified and confirmed the function of their specific copper transporters securing the main pathway of copper acquisition. Adjusting to different environments with varying copper levels during the life cycle of these organisms requires various metabolic adaptations. Using comparative proteomic analyses, measuring oxygen consumption, and enzymatic determination of NADH dehydrogenase, we showed that both amoebas respond to copper deprivation by upregulating the components of the branched electron transport chain: the alternative oxidase and alternative NADH dehydrogenase. Interestingly, analysis of iron acquisition indicated that this system is copper-dependent in N. gruberi but not in its pathogenic relative. Importantly, we identified a potential key protein of copper metabolism of N. gruberi, the homolog of human DJ-1 protein, which is known to be linked to Parkinson’s disease. Altogether, our study reveals the mechanisms underlying copper metabolism in the model amoeba N. gruberi and the fatal pathogen N. fowleri and highlights the differences between the two amoebas.